2009
DOI: 10.1021/bi9002277
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Iron−Sulfur Cluster Assembly Scaffold Protein IscU and Its Interaction with the Cochaperone HscB

Abstract: IscU is a scaffold protein that functions in iron-sulfur cluster assembly and transfer. Its critical importance has been recently underscored by the finding that a single intronic mutation in the human iscu gene is associated with a myopathy resulting from deficient succinate dehydrogenase and aconitase [Mochel, F., Knight, M. A., Tong, W. H., Hernandez, D., Ayyad, K., Taivassalo, T., Andersen, P. M., Singleton, A., Rouault, T. A., Fischbeck, K. H., and Haller, R. G. (2008) Am. J. Hum. Genet. 82, 652-660]. Isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
149
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(159 citation statements)
references
References 32 publications
10
149
0
Order By: Relevance
“…This result indicated the presence in solution of at least two species, one well folded, the second one being unfolded. The amount of the unfolded species decreased when we started adding zinc in the growth media, supporting the suggestion that this cation stabilizes the fold by compensating for the absence of the cluster and/or of the binding partner IscS [24]. The HSQC spectrum of samples prepared in this way is that of a well folded monomeric protein with well spread sharp resonances (Fig.…”
Section: Iscu Productionsupporting
confidence: 72%
“…This result indicated the presence in solution of at least two species, one well folded, the second one being unfolded. The amount of the unfolded species decreased when we started adding zinc in the growth media, supporting the suggestion that this cation stabilizes the fold by compensating for the absence of the cluster and/or of the binding partner IscS [24]. The HSQC spectrum of samples prepared in this way is that of a well folded monomeric protein with well spread sharp resonances (Fig.…”
Section: Iscu Productionsupporting
confidence: 72%
“…We recently found that apo-IscU (the protein devoid of a metal ion or Fe-S cluster) from Escherichia coli exists in solution, under reducing conditions, as a mixture of two states: one that is structured (S) and one that is dynamically disordered (D) (7). We show here that substitutions of single amino acids at conserved sites can shift the equilibrium toward either the D or the S state.…”
mentioning
confidence: 75%
“…Yeast Pim1, like Lon-type proteases in bacteria and human mitochondria, is able to recognize both unfolded (24) and folded (25) segments as "degrons," depending on the substrate protein. Adding to the challenge in understanding Isu degradation, structural studies of bacterial IscS and IscU, the orthologs of Nfs1 and Isu, respectively, found that their interaction stabilized the structure of IscU in one case and destabilized it in another (17,(26)(27)(28). Detailed in vitro analysis of Isu degradation by Pim1 are needed to identify the Isu degron recognized by Pim1.…”
Section: Discussionmentioning
confidence: 99%